(untitled) (Journal of Hama University, 2022)
This research studies the impact of GDP growth on the capital structure of private commercial banks listed on Damascus Stock Exchange, during the period (2009 to 2019). By using cross-sectional time-series data models (panel data). By Applying to a sample of banks listed on the Damascus Securities Exchange, which are (Bemo Saudi Fransi, International Trade and Finance, Syria and Diaspora, Auda). The research found the commercial banks’ keenness to strengthen their capital structure since the beginning of the war, which is a positive indication that the banks seek to strengthen their capital structure and increase their property rights to ward off risks. In addition to the impact of the GDP in Syria due to the economic conditions in Syria, where the GDP decreased at fixed prices during the study period, and the results of the standard analysis showed a direct and statistically significant effect of the growth of GDP in the capital structure of listed private commercial banks In the Damascus Stock Exchange.